2020
DOI: 10.1136/bmjresp-2020-000694
|View full text |Cite
|
Sign up to set email alerts
|

Investigating outcome measures for assessing airway clearance techniques in adults with cystic fibrosis: protocol of a single-centre randomised controlled crossover trial

Abstract: IntroductionAirway clearance techniques (ACTs) are a gold standard of cystic fibrosis management; however, the majority of research evidence for their efficacy is of low standard; often attributed to the lack of sensitivity from outcome measures (OMs) used historically. This randomised controlled trial (RCT) investigates these standard OMs (sputum weight, forced expiratory volume in 1 s) and new OMs (electrical impedance tomography (EIT), multiple breath washout (MBW) and impulse oscillometry (IOS)) to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Of note, two ongoing studies were identi ed [22,23] but publication of results of these trials is still pending. One of these trials is investigating the use of magnetic-resonance imaging (MRI) scanning compared to spirometry for ACT assessment [23], while the other compares the clinimetric properties of FEV 1 , sputum weight, impulse oscillometry, lung clearance index derived from the multiple breath washout test and electrical impedance tomography when used for ACT assessment [22].…”
Section: Primary Objective Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of note, two ongoing studies were identi ed [22,23] but publication of results of these trials is still pending. One of these trials is investigating the use of magnetic-resonance imaging (MRI) scanning compared to spirometry for ACT assessment [23], while the other compares the clinimetric properties of FEV 1 , sputum weight, impulse oscillometry, lung clearance index derived from the multiple breath washout test and electrical impedance tomography when used for ACT assessment [22].…”
Section: Primary Objective Resultsmentioning
confidence: 99%
“…Of note, two ongoing studies were identi ed [22,23] but publication of results of these trials is still pending. One of these trials is investigating the use of magnetic-resonance imaging (MRI) scanning compared to spirometry for ACT assessment [23], while the other compares the clinimetric properties of FEV 1 , sputum weight, impulse oscillometry, lung clearance index derived from the multiple breath washout test and electrical impedance tomography when used for ACT assessment [22]. We excluded a conference abstract of preliminary results from this group [20] after full text review as it reported upon feasibility and reproducibility of OMS (LCI, IOS, EIT, FEV1) across two different visits, and did not report any pre-versus post-ACT data.…”
Section: Primary Objective Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This disease, as most other lung diseases, starts in the periphery and, as it progresses, it becomes measurable with oscillometry and eventually also with spirometry. Studies are underway to determine how airway clearing techniques impact different measures of lung function, and with the advent of new drugs targeting CF more studies can be expected ( 54 , 147 ). Using oscillometry to monitor children with CF might be a reasonable approach to capture early signs of lung deterioration.…”
Section: Oscillometry Of the Normal And Diseased Lungmentioning
confidence: 99%